INDONESIAN – ENGLISH CODE MIXING USED BY ENGLISHTEACHERS IN TEACHING AND LEARNING PROCESS AT MTSN BATU BARA - Dwi Anjarsari; Willem Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research aimed to investigate the code-mixing used by the English teachers and the reasons for using it in the teaching and learning process at MTsN Batu Bara. This study used the descriptive qualitative method. The data of this research are teachers’ utterances and teachers’ reasons for using code-mixing. They were taken from the three English teachers at MTsN Batu Bara using observation and interview sheets during the teaching and learning process. The result showed three types of code-mixing used by the English teachers in the teaching and learning process. Those are Intra sentential code-mixing, Intra lexical code-mixing, and Involving change of pronunciation. From the teachers’ utterances, Intra sentential code-mixing was dominantly used in the teaching process with an average percentage of 82.5%, which occurs within word boundary. Then Intra lexical code-mixing has 11.6%, and Involving change of pronunciation has 6.4%. After doing the interview, it can be known that the teachers’ reasons for code-mixing used in the teaching and learning process are the situation of the students’ ability in learning English and bilingualism as a teachers’ ability to communicate in two languages.Keywords: Code mixing, types of code-mixing, teaching and learning process.